Effectiveness of a family-based program for post-stroke patients and families: A cluster randomized controlled trial - Saisunee Deepradit; Arpaporn Powwattana; Sunee Lagampan; Weena Thiangtham (Elsevier, 2023)
Objective: To examine the effectiveness of a family-based program for post-stroke patients and their families. Methods: A cluster randomized controlled trial design was used. Participants were randomly selected in the experimental group (3 districts) and the comparison group (3 districts), with 62 families recruited. Sixty-two persons with new stroke and families (family caregivers and family members) who met the inclusion criteria were assigned to two groups, 31 in each group. Using the Neuman System Model as a framework, we implemented the stressors assessment and family-based intervention into the program. Participants in the comparison group received usual care, and those in the experimental group underwent a stressors assessment and received the family-based program. Measurement of functional status, depression, and complications in post-stroke patients and family function in family caregivers and family members, as well as caregiver burden and caregiver stress in family caregivers, were assessed at baseline, 4 weeks, and 12 weeks after enrollment. Data analysis included descriptive statistics, the chi-square test, Bonferroni test, and repeated measures analysis of variance. Results: After participating in a 12-week family-based program, post-stroke patients in the experimental group showed statistically significant improvements in their functional status and decreased depression compared to the comparison group (P < 0.05). The family function of the experimental group was significantly improved, and caregivers' burden and stress were decreased compared to the comparison group (P < 0.05). Three patients in the experimental group and seven in the comparison group experienced complications. Conclusions: The study findings suggest that the present family-based program improved family function in family caregivers and family members and decreased caregiver burden and stress in family caregivers. The program also improved functional status and reduced depression in post-stroke patients. It is suggested the duration of the program be extended to assess its sustainable effectiveness.